Vulva Hygiene Awareness Dan Perilaku Pencegahan Kanker Serviks Pada Mahasiswa Putri Prodi Non Kesehatan - Restu Ayu Eka; Rukmana Titin Endi Wahyuni; Linatul Munawaroh (Indonesian Journal of Health Community, 2025)
Cervical cancer is one of the leading causes of cancer-related mortality among women; however, it is highly preventable through early detection and proper reproductive hygiene practices. This study aimed to analyze the relationship between knowledge of vulva hygiene awareness and cervical cancer prevention behaviors among non-health major female university students. A quantitative approach with a cross-sectional design was employed, involving 31 respondents selected through purposive sampling. Data were collected using a structured questionnaire that assessed vulva hygiene awareness and cervical cancer prevention behaviors. The results showed that 18 respondents (58.1%) had good knowledge of vulva hygiene, and the same number (58.1%) demonstrated good preventive behavior. Statistical analysis using Kendall’s Tau-b test revealed a significant relationship between vulva hygiene awareness and cervical cancer prevention behavior (p = 0.001), with a moderately strong correlation coefficient (r = 0.551). These findings suggest that higher levels of vulva hygiene knowledge are associated with better preventive behaviors. This study highlights the importance of implementing practical reproductive health education and peer-led interventions among non-health female students to promote early and sustained cervical cancer prevention.